PROBLEM OF FATIGUE IN PATIENTS WITH MULTIPLE SCLEROSIS - Michaela Miertová; Silvia Bezdeda; Anna Ovšonková; Juraj Čáp (University of Ostrava, 2017)
Aim: The aim of the study was to determine the frequency of the incidence of fatigue, and its impact on the performance of activities of daily living in patients with the diagnosis of multiple sclerosis (MS), regarding their cognitive, physical, and psychosocial functioning, and also to identify differences in the frequency of its occurrence in patients diagnosed with the disease for up to five years, and in those diagnosed for more than five years. Design: A quantitative cross-sectional study. Methods: A total of 94 MS patients with the mean age of 38.70 ± 11.20, and average disease duration of 6.5 ± 4.7, were included in the sample. An adapted version of a self-assessed questionnaire, the Modified Fatigue Impact Scale (MFIS), was used to collect empirical data. Results: Fatigue had the greatest incidence and impact on activities in the physical subscale of the used tool (19.98 ± 8.71). We identified statistically significant differences between the first group of MS patients with disease duration of up to five years, and the second group with disease duration of over five years in the physical (p = 0.019) and psychosocial subscales (p = 0.006). The group of respondents with MS for more than five years reported higher incidence of fatigue on both subscales. No significant differences were identified on the cognitive subscale. Conclusion: Objectification of the frequency of fatigue incidence - a burdensome symptom of the disease - and the monitoring of its impact on activities of daily living by means of suitable measuring instruments, such as the MFIS, contribute to a better understanding of the issue in diagnostics. It also opens up possibilities for its effective management. In terms of further research, it would be valuable to conduct validation studies of this instrument in the Slovak sociocultural environment. Keywords: fatigue, patients, multiple sclerosis, Modified Fatigue Impact Scale.